2015
DOI: 10.17770/etr2011vol2.1001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Of Invasive Flora In Cemetery Territories Of The City Of Daugavpils

Abstract: Alien species are reaching different areas, including also cemeteries. Inventory of invasive flora of cemeteries of the city of Daugavpils actually is the first such type of work to such level of detail on the Latvian scale. Field studies were conducted in 10 cemeteries of the city of Daugavpils. The obtained results are indicative of a comparatively high proportion of invasive plant species in the cemeteries. 49 invasive alien species were found. In the cemetery areas these are spreading mainly from greenerie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…1b). Our findings agree with results presented in the literature (Laiviņš & Jermacāne, 2000;Gudžinskas, 2005;Bowdler et al, 2007;Rutkovska et al, 2011) showing that cemeteries are important donor territories of alien species, e.g. of Amelanchier spicata (Lam.)…”
Section: Factors Affecting the Distribution Of Alien Species Along Rasupporting
confidence: 93%
“…1b). Our findings agree with results presented in the literature (Laiviņš & Jermacāne, 2000;Gudžinskas, 2005;Bowdler et al, 2007;Rutkovska et al, 2011) showing that cemeteries are important donor territories of alien species, e.g. of Amelanchier spicata (Lam.)…”
Section: Factors Affecting the Distribution Of Alien Species Along Rasupporting
confidence: 93%
“…Other historical sites with protection status such as archeological parks and historical gardens function also as refuge for biodiversity (Ceschin et al, 2012;Tan et al, 2010;Capotorti et al, 2013;Caneva et al, 2018;Heneidy et al, 2022). Some surveys found that urban cemeteries did indeed have a higher number of plant species than similar sized parks or urban brownfields (Graf 1986), although others revealed a high proportion of non-native (Nowinska et al, 2020;Quinton et al, 2020;Walusiak and Krzton 2021) and also invasive plant species, which mainly entered from grave or hedge greeneries (Rutkovska et al, 2011) and could also spread to the surroundings (Walusiak and Krzton 2021). Horticultural history and the use of ornamentals for landscaping are widely recognized as driving the spread of exotic species from parks and gardens to neighboring land uses (Kowarik 2005;Butenschön and Säumel 2011), as nonnative species regularly introduced as ornamentals can escape within cemeteries and to surroundings (Nowinska et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to Western European countries, few studies on invasive plant species have been conducted in Latvia during the recent decades. A few publications are based on herbarium data, while others merely studied the distribution of species (Cepurīte 2002;Priede 2008a, b, c;Rutkovska et al 2009Rutkovska et al , 2011aRutkovska et al , b, 2013Rutkovska et al , 2017Gavrilova et al 2011;Evarts-Bunders et al 2012, 2016a. A number of studies have been conducted on Reynoutria japonica Houtt.…”
Section: Introductionmentioning
confidence: 99%